Priority area identification of ecological restoration based on land use trajectory approach—Case study in a typical karst watershed - Liu, Shiliang; Dong, Yuhong; Wang, Fangfang; Liu, Hua (Frontiers in Environmental Science, 2022)
In the planning and restoration of land ecological space, the ecological restoration priority has attracted more and more attention, especially in the regions with great vulnerability. As a typical area of karst ecological area in Southwest China, Wujiang River Basin experienced human disturbance and land uses which had great impacts on the ecological environment. Based on the land use evolution from 1985 to 2019, the change of ecological-production-living land in Wujiang River Basin was analyzed by transfer matrix, intensity analysis and long-time series trajectory approaches. The results showed that from 1985 to 2019, the ecological land in Wujiang River Basin significantly decreased, while the production and living land significantly increased. The reduced ecological land was mainly transformed to cultivated land. After 1990, the intensity of land use change in Wujiang River Basin gradually increased. At the category level, the intensity of forest land change was the most stable, and the intensity levels of wasteland, shrub and grassland change were active. For the land use transition, the increased construction land was mainly from cultivated land, and the reduced forest land was mainly transformed into cultivated land. Trajectory analysis showed that the stable land use type of Wujiang River accounted for 67.36% of the total area of the basin from 1985 to 2019, and forest land was the main stable land use type. Our research spatially identified the land use change from different aspects which could be a new approach for ecological restoration. Also, our study can provide decision-making basis for the sustainable use of land resources in the study area.